Doubling the Lorenz Attractor via Coupling - Fen, Mehmet Onur (Journal of Applied Nonlinear Dynamics, 2026)
We investigate unidirectionally coupled Lorenz systems in which the drive possesses a chaotic attractor and the response admits two stable equilibrium points in the absence of the driving. It is found that double chaotic attractors coexist in the dynamics. The approach is applicable for chains of coupled Lorenz systems. The existence of four as well as eight chaotic attractors are also demonstrated. Additionally, the time evolutions of the maximum Lyapunov characteristic exponents of the systems under consideration are discussed. This is the first time in the literature that multiple chaotic attractors are obtained for coupled Lorenz systems.